Rheological processes in the slope massifs of the city of Kyiv - Reva, Maksym; Lysenko, Oleksandr; Chomko, Dmytro (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Formulation of the problem. The paper examines landslide processes that occurred on the right bank of the city of Kyiv. The authors demonstrate the general statistics of the development of landslides in the city, which is a dangerous phenomenon for the safety of the city. In Kyiv, 42 landslides have been recorded, which are in the active phase. The authors identify the main reasons for the development of landslides as engineering-geological, geomorphological conditions, climate and anthropogenic impact. The article examines the use of GIS technologies as a modern and quite effective method of monitoring landslide processes. The authors focus attention on two landslides that occurred and differ from the rest due to the atypical mechanics of the process, which was affected by the overwetting of the soil mass. It was this difference that led to this scientific research. This theoretical study was conducted on a site in the Park of Vichnoyi Slavy, since by all indicators this slope has the potential for the development of just such a landslide. Overmoistened soil mass has a special mechanics of movement on the slope and is classified as – a landslide flows.Purpose. The article examines this movement of the overmoistened soil mass on the slope as a rheological process.Methodic. The authors analyzed the theoretical foundations of soil mass behavior in such conditions, they consider it as a rheological model. The solution to the problem is based on the classical Bingham-Shvedov, Newton, and Maxwell models. The methodology for solving such tasks is given in the study. The authors investigated the necessary parameters of the soil, which are used in the construction of the calculation model. The article highlights the coefficient viscosity of soil, this coefficient deserves special attention when considering rheological processes in the soil. The considered solution model of the rheological process cannot be solved without the coefficient viscosity of soil. Using the scientific work of Ukrainian scientists, the authors determined this coefficient in the laboratory.The main material. The article investigates the possibility of a landslide occurring on one of the cultural objects in order to preserve the latter. The authors built their research on the basis of engineering investigations, which were carried out for the purpose of reconstructing the stairs in the Vichnoyi Slavy Park in Kyiv. The surveys show an engineering-geological section of the slope, which consists of 14 soil layers. The researchers established that under natural conditions this slope is in a stable state Kst=1.56. The studies have shown that at this site, with excessive moistening of the upper soil layer, a rheological process may occur. This process can develop in bulk soils (dusty sandy loam) due to its large angles of inclination and rather weak physical and mechanical properties. The article analyzes the possibility of the occurrence of rheological processes on the slopes and their role in the safety and life of the city of Kyiv.Conclusions. The calculated model is solved and shows the capture depth D=1,08 m and speed V0=0,75 m/day of movement of a potential landslide in case of overwetting of the soil on the slope in the Vichnoyi Slavy Park in the city of Kyiv.